SECUREDGE: Privacy-Preserving Deduplication with Homomorphic Encryption for Multi-Tenant Cloud Systems - Vijaya, Murala; Chakravarthy , Dr. Lade Srinivasa (International Journal of Basic and Applied Sciences, 2025)
Cloud computing developments have pushed multi-tenant models to become widely used, allowing enterprises to share computing resources ‎without mixing their data. Even though this approach works, using data deduplication to save space causes serious concerns for privacy. ‎Conventional encryption techniques may not support deduplication since they mask similar data sections and may potentially expose concealed data when processing. Our work offers a novel approach called SECUREDGE. It encrypts data using Fully Homomorphic Encryption (FHE) to ensure security. Data privacy is guaranteed by encrypting information before deduplication. It employs an FHE-based method ‎to identify and remove duplicate data without impacting the security edges between tenants. Businesses facing difficulties in the cloud may ‎rest easy with SECUREDGE’s intelligent storage solutions and state-of-the-art cryptography‎.